Dissident friendships : feminism, imperialism, and transnational solidarity - Chowdhury, Elora Halim; Philipose, Liz (Dissident feminisms., 2016)
Often perceived as unbridgeable, the boundaries that divide humanity from itself - whether national, gender, racial, political or imperial - are rearticulated through friendship. Here, Elora Chowdhury and Liz Philipose edit a collection of essays that express the different ways women forge hospitality in deference to or defiance of the structures meant to keep them apart. Emerging out of postcolonial theory, the works discuss instances when the authors have negotiated friendship's complicated, conflicted and contradictory terrain; offer fresh perspectives on feminists' invested, reluctant and selective uses of the nation; reflect on how the arts contribute to conversations about feminism, dissent, resistance and solidarity; and unpack the details of transnational dissident friendships.